1991
DOI: 10.4315/0362-028x-54.10.801
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration and Reverse Osmosis in Dairy Technology: A Review

Abstract: Ultrafiltration and reverse osmosis processes can be useful in the dairy foods industry. When milk is processed, milk fat and casein are rejected fully (e.g., are in retentate) and thus are concentrated by ultrafiltration and reverse osmosis membranes. Lactic cultures are slow to reduce the pH of retentate because of its increased buffering capacity since concentrated calcium phosphate and proteins are present. Conditions for growth of pathogenic microorganisms and inhibition of such bacteria in ultrafiltered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…Mistry and Kosikowski (1985) studied the growth of mesophilic lactic cultures in highly concentrated UF cow skim milk retentates (2.3, 2.6, 4.3 and 5.8 UF folds) and observed a higher rate of LA production with increasing UFCL of milk. Earlier studies (Mistry and Kosikowski, 1986;El-Gazzar and Marth, 1991) showed that UF milk is a better growth medium for lactic acid bacteria. In the current study also, it was noted that the acidity development is faster in yoghurt milk which was ultrafiltered.…”
Section: Chemical Composition Of Optimum Quality Yoghurtmentioning
confidence: 99%
See 1 more Smart Citation
“…Mistry and Kosikowski (1985) studied the growth of mesophilic lactic cultures in highly concentrated UF cow skim milk retentates (2.3, 2.6, 4.3 and 5.8 UF folds) and observed a higher rate of LA production with increasing UFCL of milk. Earlier studies (Mistry and Kosikowski, 1986;El-Gazzar and Marth, 1991) showed that UF milk is a better growth medium for lactic acid bacteria. In the current study also, it was noted that the acidity development is faster in yoghurt milk which was ultrafiltered.…”
Section: Chemical Composition Of Optimum Quality Yoghurtmentioning
confidence: 99%
“…Hence, it can be used to manufacture various cultured dairy products including set yoghurt. Even though, UF offers several benefits to yoghurt formulations, increase in protein and mineral content give rise to an increase in the buffering capacity of the retentates (Mistry and Kosikowski, 1985;El-Gazzar and Marth, 1991;Salaun et al, 2005) hence, slows down the fermentation of yoghurt mix or even hinder that the target pH of the final product is reached (El-Gazzar and Marth, 1991). Mistry and Kosikowski (1985) reported that, high buffering capacity places more demands on the starter culture to produce more lactic acid (LA) for the reduction of pH during fermentation of yoghurt.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of RO in the dairy industry have been reviewed by El-Gazzar and Marth (1991). Full cream or skim-milk may be concentrated by RO to a factor of 2-3 times at pressures of 2-8 MPa, the permeate essentially being pure water.…”
Section: Reverse Osmosismentioning
confidence: 99%
“…Nevertheless, it is worthwhile to examine if the literature suggests that milk UF concentration could have influenced results. It is known that the concentration of milk by UF affects the subsequent growth of lactococci in the milk blends (El Gazzar & Marth, 1991). Although some studies report greater growth of the lactococci in UF-fermented milks, due to increased buffering capacity and concentration of some nutrients (El Gazzar & Marth, 1991), others report increased doubling times (Srilaorkul et al, 1989) and lower total populations (Meijer, Tacken, Noomen, & Hugenholtz, 1995) in the fermented products.…”
Section: Lc Lactis Populationsmentioning
confidence: 99%